Prognostic value of prostate volume in non-muscle invasive bladder cancer - Won Sik Ham (Nature Portfolio, 2021)
Abstract There is evidence that a history of benign prostatic hyperplasia increases the incidence of bladder cancer, and treatment with 5-alpha reductase inhibitor or androgen deprivation therapy reduces recurrence of non-muscle invasive bladder cancer. We aimed to evaluate whether prostate volume affects its prognosis. We reviewed medical records of men who underwent transurethral resection of bladder tumor due to non-muscle invasive bladder cancer from January 2012 to December 2017. Patients were divided into two groups based on prostate volume measured by computed tomography (group 1: 264 patients with ≤ 30 mL, group 2: 124 patients with > 30 mL). Propensity score matching analysis was used for adjust selection bias, and then assessed recurrence-free survival and progression-free survival. With a median follow up duration of 52 months, group 1 showed higher 5-year recurrence-free and progression-free survival (69.3% vs 47.0%, p = 0.001; 96.7% vs 87.7%, p = 0.002). Further, cox-regression analysis showed that tumor size (HR = 1.292 p < 0.001), multifocal tumor (HR = 1.993, p < 0.001), adjuvant intravesical therapy (chemotherapy: HR = 0.580, p = 0.037 and bacillus Calmette–Guérin: HR = 0.542, p = 0.004) and prostate volume (HR = 2.326, p < 0.001) were significant predictors of recurrence-free survival. Prostate volume (HR = 2.886, p = 0.014) was also associated with PFS with age (HR = 1.043, p = 0.044) and tumor grade (HR = 3.822, p = 0.013). We conclude higher prostate volume is associated with worse recurrence and progression-free survival in non-muscle invasive bladder cancer.